Tuberous Roots an Ideal System for High Frequency In vitro Regeneration in Plumbago rosea L. (Plant Tissue Culture and Biotechnology, 2011)
Tuberous root explants of Plumbago rosea L. cultured in MS containing 3.5 mg/l BAP showed high frequency of shoot bud regeneration (62.33 ± 0.66; 0.26 ± 0.07 cm) within eight weeks. Subculture of shoot clumps (22.17 ± 0.90 shoots; 0.26 ± 0.07 cm) from the initial clump exhibited extensive rate of shoot multiplication (123.4 ± 1.029 shoots, 0.22 ± 0.01 cm) per each clump and produced a total of 369 shoots in 3.5 mg/l BAP in six weeks. Within two weeks of culture in basal liquid medium, shoot elongation (6.16 ± 0.14 cm) occurred and after three weeks  in MS solid medium supplemented with 0.1 mg/l IAA, rooting (14.7 ± 1.2) initiated on the shoots. Ninety six per cent of the rooted plants were established under the shade nethouse with regular watering.   Key words: Plumbago rosea, tuberous root, multiple shoots, High frequency   D.O.I. 10.3329/ptcb.v20i2.6915   Plant Tissue Cult. & Biotech. 20(2): 203-209, 2010 (December)